Pengembangan Website Kuis Interaktif Berbasis Gamifikasi untuk Pembelajaran PPKn pada Siswa Sekolah Dasar Nahdlatul Ulama Medan dengan Model ADDIE - Jainal Abidin; Furqan Khalidy; Demonius Sarumaha (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2026)
The teaching of Pancasila and Civic Education (PPKn) in elementary schools still faces various challenges, such as the use of conventional teaching methods, limited access to interactive media, and low student motivation. These conditions underscore the need to develop technology-based learning media that are more engaging and capable of increasing student participation. This study aims to develop a gamification-based interactive quiz website for PPKn instruction at the Nahdlatul Ulama Elementary School in Medan and to test its feasibility and effectiveness. The study employed the Research and Development (R&D) method using the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages. Data collection was conducted through observation, interviews, questionnaires, and learning outcome tests, and the data were analyzed using quantitative descriptive methods based on pretest and posttest results, as well as user evaluations. The results of the study indicate that the developed website functions well, features a user-friendly interface, and incorporates gamification elements such as points and leaderboards that effectively enhance students’ motivation to learn. Testing also demonstrated that the system is suitable for use as a digital-based PPKn learning medium. Thus, an interactive, gamified quiz website developed using the ADDIE model can serve as an effective and engaging learning tool that supports the improvement of the quality of the Civic Education learning process in elementary schools.